2006
DOI: 10.1037/0022-3514.91.2.243
|View full text |Cite|
|
Sign up to set email alerts
|

Distinguishing stereotype threat from priming effects: On the role of the social self and threat-based concerns.

Abstract: It has been argued that priming negative stereotypic traits is sufficient to cause stereotype threat. The present research challenges this assumption by highlighting the role of the social self and targets' concerns about confirming a negative group-based stereotype. Specifically, in 3 experiments the authors demonstrate that stereotype threat adversely affects the test performance and threat-based concerns of targets (but not nontargets) because only targets' social self is linked to the negative group stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 35 publications
(110 reference statements)
5
44
0
Order By: Relevance
“…Our results further demonstrated that as the social self manipulation became more direct participants saw greater overlap between themselves and their gender group. The present findings also complement our previous work examining activation of the social self in stereotype threat testing situations (see Marx & Stapel, 2006;Marx et al, 2005).…”
supporting
confidence: 88%
See 4 more Smart Citations
“…Our results further demonstrated that as the social self manipulation became more direct participants saw greater overlap between themselves and their gender group. The present findings also complement our previous work examining activation of the social self in stereotype threat testing situations (see Marx & Stapel, 2006;Marx et al, 2005).…”
supporting
confidence: 88%
“…We suggest that stereotype lift is more likely when the social self is activated in a diagnostic testing situation, because when the social self is activated the associated stereotypes are also likely to be activated; hence, non-targets should perform better due to the positive stereotype linked to their group. Support for this notion can be found in our past work on the preconditions for stereotype threat (Marx & Stapel, 2006;Marx, Stapel, & Muller, 2005). This research showed that activation of the social self led to poor test performance for stereotyped targets because their social self is linked to the negative stereotype about their group's ability.…”
Section: Stereotype Lift and The Social Selfmentioning
confidence: 66%
See 3 more Smart Citations